(untitled) (Bioscience Journal, 2018)
The aims of this study are to provide a comparative analysis of the growth and the expression of seed vigor from wheat plants subjected to periods of waterlogging during the development period. The treatments consisted of different combinations of soil waterlogging: T1 = no waterlogging; T2 = two waterlogging periods, at stages Z25 and Z45; and T3 = three waterlogging periods, at stages Z25, Z45 and Z75. Plants were collected at regular intervals after emergence until the end of the cycle: 14, 28, 42, 56, 70, 84, 98 and 112 days after emergence (DAE). Dry mass and leaf area of samples were determined. From the primary data, the analysis of growth was applied, and the total dry mass, dry matter production, relative growth and net assimilation rates, leaf area, leaf area ratio, leaf mass ratio and specific leaf area were calculated. Seedling emergence, seedling emergence rate index and dry mass of seedling shoots and roots were also evaluated. Wheat plants grown in conditions of field capacity demonstrated better performance compared to those subjected to three periods of soil waterlogging, with higher total dry mass and net assimilation rates. Seedling emergence and seedling emergence rate index did not differ between treatments. However, soil waterlogging for two or three periods resulted in a reduction in the dry matter of roots and shoots of wheat seedlings. The growth of wheat plants was found to be negatively affected by soil waterlogging. The expression of seed vigor from plants not exposed to soil waterlogging was similar to that of plant seeds subjected to soil waterlogging, although seedling growth was affected negatively by waterlogging conditions.